Failure analysis of hybrid strengthened RC square column - Vivekanandan R; Aarthi Karmegam (Građevinar)
This paper presents an analytical and experimental examination of reinforced concrete (RC) columns strengthened with a combined system of fibre-reinforced cementitious material (FRCM) and externally bonded fibre-reinforced plastics (EB-FRP). The proposed technique makes use of these advantages in enhancing the strength and minimising the premature failure of RC columns. Seven square RC columns were cast: one control column, four FRCM-strengthened columns, and two hybrid-strengthened columns. Two fibres, namely, carbon and glass fibres, were used. The columns were tested under an axial compression load in a loading frame. The ultimate strength, load vs. deformation, failure, and ductility were discussed to examine the failure and strengthening behaviour. The proposed method provided a higher confinement effect and increased capacity with fewer FRCM with EB-FRP than the other methods. Analytical predictions of the peak load were made and correlated with the experimental results.